On spectral sequences for Iwasawa adjoints à la Jannsen for families - Thomas, Oliver; Venjakob, Otmar (Arxiv, 2017)
In several spectral sequences for (global and local) Iwasawa modules over (not necessarily commutative) Iwasawa algebras (mainly of p-adic Lie groups) over Z_p are established, which are very useful for determining certain properties of such modules in arithmetic applications. ... We explain and follow the philosophy that all these spectral sequences are consequences or analogues of local cohomology and duality à la Grothendieck (and Tate for duality groups).